Messengers in providing debates within a remote online learning of university students - Dmitrenko, Natalia; Shkola, Iryna; Saliuk, Bohdana; Shkola, Oleksandr; Zakharova, Natalia (Institute of Advanced Engineering and Science, 2024)
The study aims to investigate the effectiveness of using messengers for debates within remote online and blended learning environments for university students. The research design incorporates a mixed-methods approach, combining quantitative data collection and analysis with qualitative insights. By examining the benefits, challenges, and educational achievements associated with utilizing messengers for debates, this study seeks to provide valuable insights for educators and institutions striving to enhance student engagement and learning outcomes in digital learning contexts. It is concluded that using online debates via messengers in class helps students to increase knowledge, memorize, understand and use what has been learned (students should be able to show an understanding of the points being discussed), conduct some analysis of existing messages, see things differently and express their opinion, build social competency and embrace lifelong learning.